2008
DOI: 10.1152/ajplung.00059.2008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical conjugation of ΔF508-CFTR corrector deoxyspergualin to transporter human serum albumin enhances its ability to rescue Clchannel functions

Abstract: The most common mutation of the cystic fibrosis (CF) gene, the deletion of Phe508, encodes a protein (DeltaF508-CFTR) that fails to fold properly, thus mutated DeltaF508-cystic fibrosis transmembrane conductance regulator (CFTR) is recognized and degraded via the ubiquitin-proteasome endoplasmic reticulum-associated degradation pathway. Chemical and pharmacological chaperones and ligand-induced transport open options for designing specific drugs to control protein (mis)folding or transport. A class of compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Ion channel functions were assessed by single-cell fluorescence imaging using the potential-sensitive probe, bis-(1,3-diethylthiobarbituric acid)-trimethine oxonol (DiSBAC 2 [3]; Molecular Probes, Eugene, OR), as previously reported (20), but with minor changes: fluorescence intensity was recorded by confocal laser scanning microscopy using BioRad MRC 1,024 equipped with 15 mW Ar/Kr gas laser. Maximal resolution was obtained with an Olympus plan apo 360 oil, 1.4 numerical aperture, objective lens.…”
Section: Single-cell Measurement Of Cftr and Enac Activities By Fluormentioning
confidence: 99%
“…Ion channel functions were assessed by single-cell fluorescence imaging using the potential-sensitive probe, bis-(1,3-diethylthiobarbituric acid)-trimethine oxonol (DiSBAC 2 [3]; Molecular Probes, Eugene, OR), as previously reported (20), but with minor changes: fluorescence intensity was recorded by confocal laser scanning microscopy using BioRad MRC 1,024 equipped with 15 mW Ar/Kr gas laser. Maximal resolution was obtained with an Olympus plan apo 360 oil, 1.4 numerical aperture, objective lens.…”
Section: Single-cell Measurement Of Cftr and Enac Activities By Fluormentioning
confidence: 99%
“…Other evidences suggest that the excess of calcium sequestration in ER may contribute to the abnormal trafficking of CFTRΔF508. Indeed, it has been demonstrated that the decrease and the maintenance of low calcium levels in ER, by using SERCA inhibitors, prevent the interaction between CFTRΔF508 and chaperones and thus this restores CFTRΔF508 at the plasma membrane [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these observations, a 50× excess was used in a typical preparation of targeted macromolecular paclitaxel. The results obtained show that the protein is protected by the Affi-gel matrix: the reduced thiol groups are fewer than 50% of those obtained through a solution reaction (Norez et al, 2008).…”
Section: Interaction Of Hsa With Affi-gel Blue and Its Use For 'Hetermentioning
confidence: 89%